2001
DOI: 10.1089/107999001459169
|View full text |Cite
|
Sign up to set email alerts
|

The Roles ofNramp1andTnfaGenes in Nitric Oxide Production and Their Effect on the Growth ofSalmonella typhimuriumin Macrophages fromNramp1Congenic and Tumor Necrosis Factor-α-/-Mice

Abstract: The macrophages from Nramp1 congenic mice and tumor necrosis factor (TNF)-alpha(-/-) mice were used to examine the functions of Nramp1 and Tnfa genes in nitric oxide (NO) production and Salmonella typhimurium infection. It was confirmed that the level of inducible NO synthase (iNOS)-mediated NO production in Nramp1(r) peritoneal macrophages was generally higher than that of Nramp1(s) macrophages after stimulation by interferon-gamma (IFN-gamma), lipopolysaccharide (LPS), and tumor necrosis factor-alpha (TNF-al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 47 publications
1
22
0
1
Order By: Relevance
“…Being aware of the central role of NO for host resistance against invading microbes (22,41) and the inability of Nramp1-resistant cells to exert antimicrobial effects after pharmacological blockage of NO formation (27), it is suggestive that part of the protective function of Nramp1 to control infections with intracellular pathogens such as Mycobacterium, Salmonella, or Leishmania species (27,29) can be related to its stimulatory effect toward increased and prolonged NO formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being aware of the central role of NO for host resistance against invading microbes (22,41) and the inability of Nramp1-resistant cells to exert antimicrobial effects after pharmacological blockage of NO formation (27), it is suggestive that part of the protective function of Nramp1 to control infections with intracellular pathogens such as Mycobacterium, Salmonella, or Leishmania species (27,29) can be related to its stimulatory effect toward increased and prolonged NO formation.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of NO generation and its modulation by Nramp1 for host defense against intracellular pathogens has been demonstrated by the observation that growth inhibition of mycobacteria by Nramp-resistant cells can be abrogated by the addition of iNOS inhibitors (27). Nramp1 was supposed to stabilize the mRNA of several IFN-␥-inducible genes, such as TNF-␣ (28), and TNF-␣ seems to be an important costimulus for NO production, as TNF-␣ knockout macrophages infected with S. typhimurium show no iNOS expression (29). Thus, the aim of our study was to examine the effect of Nramp1-functionality on iNOS expression and to elucidate the underlying molecular mechanism.…”
Section: N Mice Resistance To Infection With Various Intramacrophamentioning
confidence: 99%
“…Past studies have shown that Salmonella stimulates the rapid onset of tumor necrosis factor alpha (TNF-␣) following in vivo infection (15,26,39) or in vitro infection (1,11) of macrophages. TNF-␣ together with IFN-␥ activates macrophages for the enhanced killing of Salmonella (31,35).…”
mentioning
confidence: 99%
“…TNF-␣ together with IFN-␥ activates macrophages for the enhanced killing of Salmonella (31,35). Consequently, anti-TNF-␣ treatment exacerbates salmonellosis (28), resulting in diminished nitric oxide (NO) production (1). TNF-␣ has also been shown to be linked to Nramp1 gene expression (1,7).…”
mentioning
confidence: 99%
“…Con base en las características de esta familia de proteínas, se ha propuesto que el gen Nramp1 afectaría la replicación intrafagosomal de la bacteria alterando el contenido de cationes divalentes y el pH del fagosoma (Grunenheid et al, 1997). En estudios funcionales se ha demostrado que el gen Nramp1 regula la actividad antimicrobial en macrófagos de ratón, a través de la expresión de citoquinas como el factor de necrosis tumoral (TNFα) e interferón gama (IFN-γ) (Ables et al, 2001). También se ha reportado que los macrófagos de bovinos genéticamente resistentes a un desafío infeccioso in vivo con Brucella abortus (cepa 2308) son superiores en su capacidad para controlar su multiplicación bacterial intracelular, al igual que de Salmonella dublin y Mycobacterium bovis; este mecanismo es mediado también por el gen Nramp1 (Barthel et al, 2001).…”
Section: N T R O D U C C I ó Nunclassified